Late Effects in Survivors of Adolescent and Young Adult Acute Lymphoblastic Leukemia. Issue 4 (2nd April 2020) - Muffly, Lori; Maguire, Frances B; Li, Qian; Kennedy, Vanessa; Keegan, Theresa H
Abstract: Background: Knowledge regarding late effects (medical conditions and subsequent neoplasms) in survivors of adolescent and young adult (AYA) acute lymphoblastic leukemia (ALL) is lacking. Methods: Using the population-based California Cancer Registry linked with California hospitalization data, we evaluated late effects in 1069 AYAs (aged 15–39 years) diagnosed with ALL in California between 1995 and 2012 and surviving a minimum of 3 years from diagnosis. Results: The estimated 10-year cumulative incidence of subsequent endocrine disease (28.7%, 95% confidence interval [CI] = 25.8% to 31.6%) and cardiac disease (17.0%, 95% CI = 14.6% to 19.5%) were strikingly high; avascular necrosis (9.6%, 95% CI = 7.8% to 11.6%), liver disease (6.5%, 95% CI = 5.0% to 8.3%), respiratory disease (6.2%, 95% CI = 4.8% to 8.0%), seizure and/or stroke (4.3%, 95% CI = 3.1% to 5.8%), renal disease (3.1%, 95% CI = 2.1% to 4.4%), and second neoplasms (1.4%, 95% CI = 0.7% to 2.4%) were estimated to occur at 10 years with the reported frequencies. Multivariable analyses including the entire patient cohort demonstrated that public or no insurance (vs private and/or military insurance) and receipt of hematopoietic cell transplantation were independently associated with the occurrence of all late effects considered. In multivariable analyses limited to the 766 AYAs who were not transplanted, we continued to find a statistically significant association between public and no insurance and the occurrence of all late effects. Frontline regimen type (pediatric vs adult) was not statistically significantly associated with any of the late effect categories. Conclusions: This large population-based analysis is among the first to describe late effects in survivors of AYA ALL. The strong association between insurance type and late effects suggests that AYAs with public or no insurance may have reduced access to survivorship care following completion of ALL therapy.